Socio-demographic and Economic Factors Affecting Regular Charity-giving: a Case of Low-income Households in Indonesia - Laily Dwi Arsyianti; Salina Kassim; Abideen Adewale (Center of Strategic Studies (PUSKAS) BAZNAS, 2017)
A Muslim is encouraged do charity for the blessings and rewards from Allah subhanahuwata’ala, not limited to low-income households. Some social finance institutions have been encouraging their zakat and infaq recipients, along with empowering programmes, to gradually give away a portion of their income as charity to the institutions; thus, it would be circulated among them. It is necessary to identify what factors influence them in regularly giving charity. Questionnaires were distributed to 1780 respondents from six areas in the west, middle, and east of Indonesia. By employing logistic regression, results show that determinants affecting regular charity giving of low-income households in Indonesia are employment status, household size, portion of charity per income, expectation of future economy, income, religious activity, and type of financing institution. Many Islamic economic researches have looked at compulsory charity, that is, zakat, and waqf topics, but none of them has covered voluntary monetary charity giving of low-income households in Indonesia. This research tries to fill the gap. Keywords: charity giving, low-income households, Indonesia, social finance